Flame-retardant chemical crosslinking polyolefin foaming material with high foaming ratio
By using bromine flame retardant and antimony trioxide/wollastite composite powder, combined with a crosslinking agent and an antioxidant, the problem of excessive foaming agent residue in polyolefin foam exceeds the standard and apparent unevenness, achieving high foaming ratio and excellent flame retardant performance.
Patent Information
- Application Number
- CN202411981129.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-31
- Publication Date
- 2025-03-25
- Estimated Expiration
- 2044-12-31
AI Technical Summary
The residual amount of azodiformamide in the existing polyolefin foam exceeds the standard, and the polyolefin foam with high foaming ratio is not flat, and there are problems such as bubbles or holes.
Bromine-based flame retardant and antimony trioxide/wollastite composite powder are used as flame retardant. By regulating the average particle size and coverage of nanoantimonium trioxide, the mass ratio of flame retardant is optimized, and combined with accelerating crosslinking agent and antioxidant, chemical crosslinking polyolefin foaming materials with high foaming ratio and flame retardant are prepared.
The high foaming ratio and excellent flame retardant properties of polyolefin foaming materials are achieved, and the problems of excessive foaming agent residues and apparent unevenness are avoided, and the requirements of relevant regulations are met.
Smart Images

Figure CN119684701A_ABST
Abstract
Description
Technical Field
[0001] The present application belongs to the field of polyolefin foaming materials, and more specifically, relates to a chemically cross-linked polyolefin foaming material with high foaming ratio and flame retardancy. Background Art
[0002] Chemically cross-linked polyolefin foam material is a foam material that forms a three-dimensional network structure between polyolefin molecular chains through chemical reactions, wherein the three-dimensional network structure can enhance the physical and mechanical properties and heat resistance of the material. For chemically cross-linked polyolefin foam materials, halogen flame retardants and antimony flame retardants are usually compounded to improve the flame retardant properties of the foam material. However, in the actual production process, it is found that antimony flame retardants can cause appearance problems in polyolefin foams with high foaming ratios, such as rough surfaces, a large number of bubbles, and even broken holes. In addition, when the foaming ratio of polyolefin foam is unstable, the use of flame retardants compounded with halogen flame retardants and antimony flame retardants will make the overall appearance of the polyolefin uneven, which is not conducive to use. At the same time, there is a phenomenon of excessive residual content of the foaming agent azodicarbonamide, which does not meet the requirements of relevant regulations. Summary of the invention
[0003] In view of the defects of the prior art, the purpose of this application is to provide a high foaming ratio and flame retardant chemically cross-linked polyolefin foam material, aiming to solve the problems of excessive residual amount of azodicarbonamide (more than 0.1%) of the existing polyolefin foam, and uneven surface, bubbles and even holes in the high foaming ratio polyolefin foam.
[0004] To achieve the above object, the present application provides a high foaming ratio and flame retardant chemically cross-linked polyolefin foam material, which includes a flame retardant, The flame retardant includes a brominated flame retardant and an antimony trioxide / wollastonite composite powder; in the antimony trioxide / wollastonite composite powder, nano antimony trioxide is attached to the surface of wollastonite by physical adsorption, and the surface area covered by the nano antimony trioxide accounts for 40% or more of the total surface area of wollastonite.
[0005] Preferably, the brominated flame retardant is selected from one or more of decabromodiphenyl ether, decabromodiphenyl ethane, tetrabromobisphenol A, hexabromocyclododecane, brominated epoxy resin and octabromoether.
[0006] Preferably, in the antimony trioxide / wollastonite composite powder, the surface area covered by the nano antimony trioxide accounts for 40% to 75% of the total surface area of the wollastonite. Further preferably, the average particle size of the nano antimony trioxide is 100 to 500 nm, and the mesh size of the wollastonite is 300 to 600 mesh.
[0007] Preferably, the mass ratio of the brominated flame retardant to the antimony trioxide / wollastonite composite powder is (1-3):1.
[0008] Preferably, the raw materials for preparing the chemically cross-linked polyolefin foaming material further include polyolefin, foaming agent, cross-linking agent, co-cross-linking agent, and antioxidant. Further preferably, the mass ratio of the polyolefin, foaming agent, cross-linking agent, co-cross-linking agent, antioxidant, and flame retardant is (60-70):(10-20):(0.1-1):(0.5-1.5):(0.2-0.5):(5-15).
[0009] Preferably, the polyolefin has a melt index of 0.5-5 g / 10 min and a density of 0.85-0.98 g / cm 3 , selected from one or more of low-density polyethylene, medium-density polyethylene, high-density polyethylene, metallocene polyethylene, ethylene-octene copolymer, ethylene-butene copolymer and ethylene-vinyl acetate copolymer.
[0010] Preferably, the crosslinking agent is selected from one or more of dibenzoyl peroxide, diisopropyl di-tert-butyl peroxide, diisopropyl peroxide, diacetyl peroxide, tert-butyl peroxypivalate, and diphenyl peroxydicarbonate.
[0011] Preferably, the auxiliary cross-linking agent is selected from one or more of trimethylolpropane trimethacrylate, triallyl cyanurate, triallyl isocyanurate, and trimethylolpropane triacrylate.
[0012] Preferably, the antioxidant is selected from one or more of antioxidants CA, 330, 1010, and 1076.
[0013] Preferably, the above-mentioned raw materials for preparation further include a functional flame retardant; the above-mentioned functional flame retardant includes one or more of nano silicon dioxide, magnesium oxide, aluminum oxide, a silane coupling agent and pentaerythritol stearate.
[0014] The chemically cross-linked polyolefin foam material provided in the present application has a foaming ratio of 25 to 45; the chemically cross-linked polyolefin foam material meets the UL94 horizontal combustion HF-1 grade, and the sum of the afterflame time and the afterglow time is ≤15s.
[0015] In a second aspect, the present application also provides a method for preparing the above-mentioned chemically cross-linked polyolefin foam material, comprising the following steps: S1, mixing and kneading part of the above polyolefin and the above cross-linking agent, auxiliary cross-linking agent, antioxidant, and flame retardant to obtain semi-formulated particles; S2, mixing and kneading the remaining polyolefin and the blowing agent to obtain expanded particles; S3, extruding the semi-formulated particles and the expanded particles to obtain a sheet; S4, foaming the sheet material to obtain a chemically cross-linked polyolefin foam material.
[0016] Preferably, the temperature of the mixing and kneading in step S2 and the temperature of the extrusion molding in step S3 are both lower than the decomposition temperature of the foaming agent, and the temperature of the foaming in step S4 is higher than the decomposition temperature of the foaming agent.
[0017] Preferably, the foaming temperature in step S4 is 240°C to 260°C.
[0018] In general, the above technical solutions conceived by this application have the following technical advantages compared with the prior art: (1) The chemically cross-linked polyolefin foam material provided in the present application can improve the flame retardancy of the polyolefin foam material while improving the foaming ratio by adding antimony trioxide / wollastonite composite powder as a flame retardant, and regulating the average particle size of nano antimony trioxide in the antimony trioxide / wollastonite composite powder, the coverage of nano antimony trioxide on the surface of wollastonite, and the mass ratio of the bromine flame retardant and antimony trioxide / wollastonite composite powder, thereby preparing a polyolefin foam material with a smooth surface, high foaming ratio and flame retardancy. In addition, the above-mentioned flame retardant can cooperate with other components such as co-crosslinking agents and antioxidants, so that the polyolefin material will not break when undergoing high-temperature foaming, and the foaming agent is completely decomposed at high temperature, which can effectively solve the problem of excessive residual azodicarbonamide in the foaming agent.
[0019] (2) The present application adds a functional flame retardant to cooperate with the above-mentioned brominated flame retardant and antimony trioxide / wollastonite composite powder to exert a synergistic flame retardant effect, thereby improving the flame retardant effect of the foaming material and ensuring that the polyolefin foaming material has excellent flame retardant properties. BRIEF DESCRIPTION OF THE DRAWINGS
[0020] Figure 1 is the appearance of the chemically cross-linked polyolefin foam material prepared in Example 1 of the present application; Figure 2 This is the appearance of the chemically cross-linked polyolefin foam material prepared in Comparative Example 6 of the present application. DETAILED DESCRIPTION
[0021] In order to make the purpose, technical solution and advantages of the present application more clearly understood, the present application is further described in detail below in conjunction with the accompanying drawings and embodiments. It should be understood that the specific embodiments described herein are only used to explain the present application and are not used to limit the present application.
[0022] In the description of this application, the term "and / or" is a description of the association relationship of associated objects, indicating that three relationships may exist. For example, A and / or B can represent: A exists alone, A and B exist at the same time, and B exists alone. The symbol " / " herein indicates that the associated objects are in an or relationship, for example, A / B means A or B.
[0023] In the description of the embodiments of the present application, words such as "exemplary" or "for example" are used to indicate examples, illustrations or descriptions. Any embodiment or design described as "exemplary" or "for example" in the embodiments of the present application should not be interpreted as being more preferred or more advantageous than other embodiments or designs. Specifically, the use of words such as "exemplary" or "for example" is intended to present related concepts in a specific way.
[0024] In the description of the embodiments of the present application, unless otherwise specified, “plurality” means two or more than two.
[0025] Unless otherwise indicated, all numerical values used in the specification and claims to express the amount of components, reaction conditions, etc. are understood to be modified by the term "about". Therefore, unless otherwise indicated, the numerical parameters set forth herein are approximate values that can vary according to the desired performance required. Numerical ranges represented by endpoints include all numbers within the range and any range within the range, for example, 5 to 15 include 5, 6.5, 8, 9, 12, 14 and 15, etc.
[0026] The foaming agent used in conventional polyolefin foam is an azo foaming agent. In actual production, it is found that when the bromine antimony flame retardant with good flame retardant effect on the market and the azo foaming agent are mixed and foamed to prepare flame-retardant polyolefin foaming materials, the surface of the foaming material is rough and large bubbles or broken holes appear. This may be because the addition of bromine antimony flame retardants causes the azo foaming agent to decompose in advance, so that the decomposed gas expands when heated during foaming and concentrates on the surface, thereby forming large foaming holes on the surface of the material. At the same time, the foaming state of the foaming material is poor, the foaming ratio is lower than 25, and a polyolefin foaming material with a high foaming ratio (foaming ratio of 25~45) cannot be prepared. In addition, there is also a phenomenon that the residual amount of the foaming agent azodicarbonamide exceeds the standard. The technicians in this field usually choose to increase the foaming temperature so that the foaming agent azodicarbonamide is completely decomposed to solve the above problem, but the ordinary chemical cross-linked polyolefin material will have different degrees of fracture in the high-temperature foaming process, which does not meet the production requirements. Based on this, the present application provides a high foaming ratio and flame retardant chemically cross-linked polyolefin foam material, which includes a flame retardant, The flame retardant includes a brominated flame retardant and an antimony trioxide / wollastonite composite powder. In the antimony trioxide / wollastonite composite powder, nano antimony trioxide is attached to the surface of wollastonite by physical adsorption, and the surface area covered by the nano antimony trioxide accounts for 40% or more of the total surface area of wollastonite.
[0027] It is understandable that a person skilled in the art can distinguish nano antimony trioxide from wollastonite by setting a suitable grayscale threshold based on the scanning electron microscope image of the antimony trioxide / wollastonite composite powder and the grayscale difference between nano antimony trioxide and wollastonite in the image through an image processing method, and then calculate the ratio of the surface area covered by nano antimony trioxide to the total surface area of wollastonite, i.e., the coverage rate of nano antimony trioxide on the surface of wollastonite, through image analysis software.
[0028] In some embodiments, the brominated flame retardant is selected from one or more of decabromodiphenyl ether, decabromodiphenyl ethane, tetrabromobisphenol A, hexabromocyclododecane, brominated epoxy resin and octabromoether.
[0029] In some embodiments, the mass percentage of bromine in the brominated flame retardant is 80% to 85%, and the particle size is 1 to 2 μm.
[0030] It is to be understood that the present application does not limit the source of the above-mentioned antimony trioxide / wollastonite composite powder, and it can be prepared by methods known to those skilled in the art. In some embodiments, the above-mentioned antimony trioxide / wollastonite composite powder is made of wollastonite and antimony trichloride as raw materials, and is hydrolyzed in an alkaline environment under the action of a surfactant, and then filtered, washed, and dried to prepare an antimony trioxide / wollastonite composite powder. By adjusting the mass ratio of antimony trichloride and wollastonite, the amount of surfactant, the temperature and time of the hydrolysis reaction, etc., the average particle size of nano antimony trioxide in the antimony trioxide / wollastonite composite powder and the coverage of nano antimony trioxide on the surface of wollastonite can be regulated.
[0031] In some embodiments, in order to make the hydrolysis reaction more fully proceed and the reaction complete, the above-mentioned wollastonite can be dispersed in water to form a wollastonite suspension, the above-mentioned antimony trichloride is first dissolved in a hydrochloric acid solution to obtain an antimony trichloride hydrochloric acid solution, and then the antimony trichloride hydrochloric acid solution is hydrolyzed in an alkaline environment under the action of a surfactant to generate nano antimony trioxide, which is uniformly attached to the surface of the wollastonite. It is understandable that the present application has no special restrictions on the composition and shape of the above-mentioned wollastonite, and the wollastonite reported in the prior art that is suitable for the field of polyolefin foaming materials is suitable for the present application. The wollastonite used in the specific embodiments of the present application is needle-shaped wollastonite.
[0032] In some embodiments, the mass ratio of the antimony trichloride to the wollastonite is (0.5~1):1.
[0033] In some embodiments, the surfactant may be, but is not limited to, polyethylene glycol (PEG). In some embodiments, the molecular weight of the polyethylene glycol is 1000-10000, and exemplary, the molecular weight of the polyethylene glycol is 2000, 4000, 6000, etc. In some embodiments, the mass ratio of the polyethylene glycol to the wollastonite is (0.002-0.01):1.
[0034] In some embodiments, the pH of the alkaline environment is 7-8, in order to facilitate the hydrolysis reaction. During the experiment, alkaline reagents such as ammonia water and sodium hydroxide can be used to control the pH.
[0035] In some embodiments, the temperature of the hydrolysis reaction is 40° C. to 50° C., and the time of the hydrolysis reaction is 0.5 to 1 h.
[0036] In some embodiments, in the antimony trioxide / wollastonite composite powder, the surface area covered by the nano antimony trioxide accounts for 40% to 75% of the total surface area of the wollastonite. In some embodiments, the average particle size of the nano antimony trioxide is 100 to 500 nm, and the mesh size of the wollastonite is 300 to 600 mesh.
[0037] In some embodiments, the mass ratio of the brominated flame retardant to the antimony trioxide / wollastonite composite powder is (1-3):1.
[0038] The present application adds antimony trioxide / wollastonite composite powder as a flame retardant component, which can replace traditional antimony flame retardants such as antimony trioxide, effectively reduce the contact between antimony flame retardants and foaming agents, thereby avoiding premature decomposition of the foaming agent during mixing and kneading, and can effectively inhibit the generation of large bubbles or pores on the surface of the foamed material. At the same time, by regulating the average particle size of nano antimony trioxide in the antimony trioxide / wollastonite composite powder, the coverage of nano antimony trioxide on the surface of wollastonite, and the mass ratio of the bromine flame retardant and the antimony trioxide / wollastonite composite powder, the flame retardant properties of the polyolefin foam material can be improved while the foaming ratio can be improved, and a polyolefin foam material with a smooth surface, high foaming ratio and flame retardancy can be prepared.
[0039] In some embodiments, the raw materials for preparing the chemically cross-linked polyolefin foaming material further include polyolefin, foaming agent, cross-linking agent, co-cross-linking agent, and antioxidant. In a preferred embodiment, the mass ratio of the polyolefin, foaming agent, cross-linking agent, co-cross-linking agent, antioxidant, and flame retardant is (60-70): (10-20): (0.1-1): (0.5-1.5): (0.2-0.5): (5-15).
[0040] In some embodiments, the polyolefin has a melt index of 0.5 to 5 g / 10 min and a density of 0.85 to 0.98 g / cm 3 In some embodiments, the polyethylene may be selected from one or more of low-density polyethylene, medium-density polyethylene, high-density polyethylene, metallocene polyethylene, ethylene-octene copolymer, ethylene-butene copolymer and ethylene-vinyl acetate copolymer.
[0041] In some embodiments, the density of the low-density polyethylene is 0.910-0.925 g / cm 3 The density of the above medium density polyethylene is 0.926~0.940g / cm 3 The density of the high-density polyethylene is 0.941~0.965g / cm 3 .
[0042] In some embodiments, the gas evolution amount of the foaming agent is 210-230 mL / g. The present application does not limit the type of the foaming agent, and a foaming agent with low cost and good foaming effect is preferred, such as azodicarbonamide.
[0043] In some embodiments, the crosslinking agent is selected from one or more of dibenzoyl peroxide, diisopropyl di-tert-butyl peroxide, diisopropyl peroxide, diacetyl peroxide, tert-butyl peroxypivalate, and diphenyl peroxydicarbonate.
[0044] In some embodiments, the auxiliary cross-linking agent is selected from one or more of trimethylolpropane trimethacrylate, triallyl cyanurate, triallyl isocyanurate and trimethylolpropane triacrylate.
[0045] In the present application, the antioxidant can improve the antioxidant performance of the foaming material during processing and use, and increase the service life. In some embodiments, the antioxidant includes but is not limited to one or more of antioxidants CA, 330, 1010, and 1076.
[0046] The present application adds a cross-linking agent and an antioxidant to compound with other components, so that the chemically cross-linked polyolefin material will not break during high-temperature foaming (the foaming temperature is 240°C~260°C). At the same time, the foaming agent can be completely decomposed at high temperature, effectively solving the problem of excessive azodicarbonamide residues.
[0047] In some embodiments, the raw materials for preparation further include a functional flame retardant. The functional flame retardant includes but is not limited to one or more of nano silicon dioxide, magnesium oxide, aluminum oxide, silane coupling agent and pentaerythritol stearate. The present application can cooperate with the brominated flame retardant and antimony trioxide / wollastonite composite powder to play a synergistic flame retardant role by adding a functional flame retardant, thereby improving the flame retardant effect of the foaming material and ensuring that the polyolefin foaming material has excellent flame retardant properties.
[0048] In some embodiments, the mass ratio of the above-mentioned polyolefin, foaming agent, cross-linking agent, co-cross-linking agent, antioxidant, flame retardant, and functional flame retardant is (60~70):(10~20):(0.1~1):(0.5~1.5):(0.2~1):(5~15):(0~5).
[0049] On the other hand, the present application also provides a method for preparing the above-mentioned chemically cross-linked polyolefin foam material, comprising the following steps: S1, mixing part of the above polyolefin and the above cross-linking agent, auxiliary cross-linking agent, antioxidant, and flame retardant, kneading and then extruding and granulating to obtain semi-formulated particles; S2, mixing the remaining polyolefin and the foaming agent, kneading and then extruding and granulating to obtain foamed particles; S3, extruding the semi-formulated particles and the expanded particles to obtain a sheet; S4, foaming the sheet material to obtain a chemically cross-linked polyolefin foam material.
[0050] In some embodiments, step S1 is: mixing and kneading part of the polyolefin with the crosslinking agent, the auxiliary crosslinking agent, the antioxidant, and the flame retardant, and then extruding and granulating to obtain semi-formulated particles. In some embodiments, the mixing and kneading temperature in step S1 is 120° C. to 150° C., and the mixing and kneading time is 20 to 30 minutes.
[0051] In a specific embodiment of the present application, step S1 is: mixing and kneading part of the polyolefin and the antioxidant and the flame retardant, the kneading temperature is 140℃~150℃, the kneading time is 8~14min, and then the kneaded material mass is discharged into a single screw extruder granulator, and the flame retardant masterbatch A is obtained through extrusion, drawing, pelletizing, and drying processes; then the flame retardant masterbatch A is mixed and kneaded with a crosslinking agent and an auxiliary crosslinking agent, the kneading temperature is 120℃~125℃, the kneading time is 10~15min, and then discharged into a single screw extruder granulator, and the semi-formulated particles are obtained through extrusion, drawing, pelletizing, and drying processes. It is understandable that those skilled in the art can adaptably adjust the temperature and time of the mixing and kneading according to the mixing of the raw materials, which are all within the scope of protection of the present application.
[0052] In some embodiments, the process conditions of the extrusion granulation in step S1 may be: screw speed 5.85-7.85 rpm, the temperature of each section is: the temperature of zone 1 is 102°C-112°C, the temperature of zone 2 is 111°C-121°C, the temperature of zone 3 is 110°C-120°C, the temperature of zone 4 is 114°C-124°C, and the temperature of zone 5 is 115°C-125°C. It is understood that, according to the specific type and amount of the selected polyolefin raw material, as well as the different laboratory extrusion granulators, the screw speed can be increased / decreased adaptively, and the temperature of each section can be increased / decreased adaptively, which are all within the protection scope of this application.
[0053] In some embodiments, the temperature of the mixing and kneading in step S2 and the temperature of the extrusion molding in step S3 are both lower than the decomposition temperature of the above-mentioned foaming agent, in order to avoid premature decomposition of the foaming agent, thereby affecting the performance of the foaming material. In some embodiments, the temperature of the mixing and kneading in step S2 is 120°C to 125°C, and the time is 10 to 15 minutes. In some embodiments, the temperature of the extrusion molding in step S3 is 85°C to 115°C.
[0054] In the specific embodiment of the present application, the process conditions for extrusion molding in step S3 are: screw speed 4.6~6.6rpm, and the temperature of each section is: zone 1 temperature is 85℃~95℃, zone 2 temperature is 101℃~111℃, zone 3 temperature is 100℃~110℃, and zone 4 temperature is 104℃~114℃. In practical applications, the extrusion molding temperature can be increased or decreased according to the specific type of the selected foaming agent, which is within the protection scope of the present application.
[0055] In some embodiments, the foaming temperature in step S4 is higher than the decomposition temperature of the foaming agent, so as to fully foam the foaming agent in the sheet. In some embodiments, the foaming temperature in step S4 is 240°C to 260°C.
[0056] The chemical cross-linked polyolefin foam material provided in the present application has a foaming ratio of 25 to 45. The chemical cross-linked polyolefin foam material is subjected to a UL94 horizontal combustion test, and the flame retardant performance meets the UL94 horizontal combustion HF-1 level, and the sum of the afterflame time and the afterglow time is ≤15s. The chemical cross-linked polyolefin foam material provided in the present application has a high foaming ratio, excellent flame retardant performance, and the azo foaming agent is completely decomposed, which solves the problem of excessive azodicarbonamide residues and meets the requirements of relevant regulations.
[0057] It should be understood that materials of the same or similar type, model, quality, nature or function as the reagents and instruments used in the following examples can be used to implement the present application. The experimental methods used in the following examples are conventional methods unless otherwise specified. The materials, reagents, etc. used in the following examples can be obtained from commercial sources unless otherwise specified.
[0058] The following are examples and comparative examples: Example 1 References for the preparation method of antimony trioxide / wollastonite composite powder (Yang Yong et al., Preparation of wollastonite-antimony trioxide composite particles and their application in PA6. Journal of Chemical Engineering of Universities, 2014, 28(6), 1302-1308). Specifically, 20 g of 400-mesh needle-shaped wollastonite was dispersed in 100 mL of water to prepare a wollastonite suspension, 14 g of antimony trichloride was dissolved in 100 mL of hydrochloric acid solution to prepare an antimony trichloride hydrochloric acid solution, the above-mentioned wollastonite suspension and the above-mentioned antimony trichloride hydrochloric acid solution were completely mixed, and then 0.2 g of surfactant PEG2000 was added, and the pH of the mixed solution was adjusted to 7 with ammonia water, and the mixture was reacted at 40° C. for 1 hour, and then filtered, washed, and dried to obtain an antimony trioxide / wollastonite composite powder, wherein nano antimony trioxide was attached to the surface of wollastonite by physical adsorption, the coverage rate of nano antimony trioxide on the surface of wollastonite was 58%, the average particle size of nano antimony trioxide was 230 nm, and the mesh number of wollastonite was 400 mesh.
[0059] The components and mass fractions of the chemically cross-linked polyolefin foam material provided in this embodiment are as follows: 65 parts of polyolefin (low-density polyethylene, density of 0.922g / cm³, melt index of 1.9g / 10min, purchased from Lanzhou Petrochemical 2426H), 15 parts of foaming agent (ADC foaming agent of Sop Group, gas emission of 215mL / g), 0.5 parts of cross-linking agent (diisopropylbenzene peroxide, 1 min decomposition half-life temperature of 178°C, purchased from Hefei Anbang Chemical Co., Ltd.), 1 part of auxiliary cross-linking agent (trimethylolpropane trimethacrylate, specific gravity of 1.061g / cm³, purchased from Shanghai Dunmei New Materials), 0.5 parts of antioxidant (antioxidant 1010), 8 parts of brominated flame retardant (decabromodiphenylethane, particle size 1.5μm, mass percentage of bromine 85%), 4 parts of the above-mentioned antimony trioxide / wollastonite composite powder, and 3 parts of functional flame retardant (environmentally friendly flame retardant synergist brand FS-707R, purchased from Ruike New Materials).
[0060] The preparation method of the chemically cross-linked polyolefin foam material comprises the following steps: 1) 30 parts of polyolefin, brominated flame retardant, antimony trioxide / wollastonite composite powder, functional flame retardant and antioxidant were mixed and kneaded in a 145°C kneading bin for 12 minutes, and then the kneaded material mass was discharged into a single screw extruder granulator by forced feeding. The screw speed was 6.85 rpm, and the temperatures of each zone were: 107°C in zone 1, 116°C in zone 2, 115°C in zone 3, 119°C in zone 4, and 120°C in zone 5. Flame retardant masterbatch A was obtained by granulation.
[0061] 2) The flame retardant masterbatch A, the crosslinking agent and the auxiliary crosslinking agent are placed in a 120°C mixing bin and mixed for 13 minutes, and then discharged into a single screw extruder granulator. The screw speed is 6.85 rpm, and the temperatures of each zone are: 107°C in zone 1, 116°C in zone 2, 115°C in zone 3, 119°C in zone 4, and 120°C in zone 5. Semi-formulated particles are obtained by granulation.
[0062] 3) 35 parts of polyolefin and foaming agent were placed in a 120°C mixing bin and mixed for 15 minutes, and then put into a single-screw extruder granulator. The screw speed was 6.85 rpm, and the temperatures of each zone were: 107°C for zone 1, 116°C for zone 2, 115°C for zone 3, 119°C for zone 4, and 120°C for zone 5. Granulation was performed to obtain foamed particles.
[0063] 4) The semi-formulated particles and the foamed particles are premixed and put into a single screw extruder. The screw speed is 5.6 rpm. The temperatures of each zone are: 90°C in zone 1, 106°C in zone 2, 105°C in zone 3, and 109°C in zone 4 to obtain a sheet, i.e., a pre-foamed body.
[0064] 5) The pre-foamed body is placed in a high-temperature foaming furnace at 250°C for foaming to obtain a porous polyolefin foamed material having a multi-layer cellular structure, which has a smooth surface and no bubbles, such as Figure 1 shown.
[0065] Example 2 The components and mass fractions of the chemically cross-linked polyolefin foam material provided in this embodiment are as follows: 65 parts of polyolefin (low-density polyethylene, density 0.922 g / cm³, melt index 1.9 g / 10 min, purchased from Lanzhou Petrochemical 2426H), 18 parts of foaming agent (ADC foaming agent of Sopo Group, gas emission 215 mL / g), 0.5 parts of cross-linking agent (diisopropyl peroxide, 1 min decomposition half-life temperature 178 ℃, purchased from Hefei Anbang Chemical Co., Ltd.), 1 part of a cross-linking agent (trimethylolpropane trimethacrylate, with a specific gravity of 1.061g / cm³, purchased from Shanghai Dunmei New Materials), 0.5 parts of an antioxidant (antioxidant 1010), 7.5 parts of a brominated flame retardant (decabromodiphenylethane, with a particle size of 1μm and a mass percentage of bromine of 80%), and 7.5 parts of antimony trioxide / wollastonite composite powder (the mesh number of wollastonite is 600 mesh, the average particle size of nano antimony trioxide is 100nm, and the coverage rate of nano antimony trioxide on the surface of wollastonite is 40%). The preparation method of the above antimony trioxide / wollastonite composite powder is the same as that of Example 1, wherein the amount of 600 mesh needle-shaped wollastonite is 20g, the amount of antimony trichloride is 10g, the amount of surfactant PEG2000 is 0.05g, the reaction temperature is 45℃, and the reaction time is 0.5h.
[0066] The preparation method of the chemically cross-linked polyolefin foam material comprises the following steps: 1) 30 parts of polyolefin, brominated flame retardant, antimony trioxide / wollastonite composite powder, functional flame retardant and antioxidant were mixed and kneaded in a 150°C kneading bin for 9 minutes, and then the kneaded material mass was discharged into a single-screw extruder granulator by forced feeding. The screw speed was 5.85 rpm, and the temperatures of each zone were: 112°C for zone 1, 121°C for zone 2, 120°C for zone 3, 124°C for zone 4, and 125°C for zone 5. Flame retardant masterbatch A was obtained by granulation.
[0067] 2) The flame retardant masterbatch A, the crosslinking agent and the auxiliary crosslinking agent are placed in a 122°C mixing bin and mixed for 12 minutes, and then discharged into a single screw extruder granulator. The screw speed is 5.85 rpm, and the temperatures of each zone are: 112°C in zone 1, 121°C in zone 2, 120°C in zone 3, 124°C in zone 4, and 125°C in zone 5. Semi-formulated particles are obtained by granulation.
[0068] 3) 35 parts of polyolefin and foaming agent were placed in a 120°C mixing bin and mixed for 15 minutes, and then put into a single-screw extruder granulator. The screw speed was 5.85 rpm, and the temperatures of each zone were: zone 1 112°C, zone 2 121°C, zone 3 120°C, zone 4 125, zone 5 125°C, and granulation was performed to obtain foamed particles.
[0069] 4) The semi-formulated particles and the foamed particles are premixed and put into a single screw extruder at a screw speed of 4.6 rpm and a temperature of: 95°C in zone 1, 111°C in zone 2, 110°C in zone 3, and 114°C in zone 4 to obtain a sheet, i.e., a pre-foamed body.
[0070] 5) The pre-foamed body is placed in a high-temperature foaming furnace at 240° C. for foaming to obtain a polyolefin foamed material.
[0071] Example 3 The components and mass fractions of the chemically cross-linked polyolefin foam material provided in this embodiment are as follows: 65 parts of polyolefin (low-density polyethylene, density 0.922 g / cm³, melt index 1.9 g / 10 min, purchased from Lanzhou Petrochemical 2426H), 12 parts of foaming agent (ADC foaming agent of Sopo Group, gas emission 215 mL / g), 0.5 parts of cross-linking agent (diisopropyl peroxide, 1 min decomposition half-life temperature 178 ℃, purchased from Hefei Anbang Chemical Co., Ltd.), 1 part of a cross-linking agent (trimethylolpropane trimethacrylate, with a specific gravity of 1.061g / cm³, purchased from Shanghai Dunmei New Materials), 0.5 parts of an antioxidant (antioxidant 1010), 7.5 parts of a brominated flame retardant (decabromodiphenylethane, with a particle size of 2μm and a mass percentage of bromine of 85%), 7.5 parts of antimony trioxide / wollastonite composite powder (the mesh number of wollastonite is 400 mesh, the average particle size of nano antimony trioxide is 140nm, and the coverage rate of nano antimony trioxide on the surface of wollastonite is 47%), and 5 parts of a functional flame retardant (nano silicon dioxide, with an average particle size of 35nm). The preparation method of the antimony trioxide / wollastonite composite powder is the same as that in Example 1, wherein the amount of 400 mesh needle-shaped wollastonite is 20 g, the amount of antimony trichloride is 12 g, the amount of surfactant PEG2000 is 0.06 g, the reaction temperature is 40° C., and the reaction time is 0.5 h.
[0072] The preparation method of the chemically cross-linked polyolefin foam material comprises the following steps: 1) 35 parts of polyolefin, brominated flame retardant, antimony trioxide / wollastonite composite powder, functional flame retardant and antioxidant were mixed and kneaded in a 140°C kneading bin for 14 minutes, and then the kneaded material mass was discharged into a single screw extruder granulator by forced feeding. The screw speed was 7.85 rpm, and the temperatures of each zone were: 102°C for zone 1, 111°C for zone 2, 110°C for zone 3, 114°C for zone 4, and 115°C for zone 5. Flame retardant masterbatch A was obtained by granulation.
[0073] 2) The flame retardant masterbatch A, the crosslinking agent and the auxiliary crosslinking agent are placed in a 125°C mixing bin and mixed for 10 minutes, and then discharged into a single screw extruder granulator. The screw speed is 7.85 rpm, and the temperatures of each zone are: 102°C in zone 1, 111°C in zone 2, 110°C in zone 3, 114°C in zone 4, and 115°C in zone 5. Semi-formulated particles are obtained by granulation.
[0074] 3) 30 parts of polyolefin and foaming agent were placed in a 120°C mixing bin and mixed for 15 minutes, and then put into a single-screw extruder granulator. The screw speed was 7.85 rpm. The temperatures of each zone were: 102°C for zone 1, 111°C for zone 2, 110°C for zone 3, 114°C for zone 4, and 115°C for zone 5. Granulation was performed to obtain foamed particles.
[0075] 4) The semi-formulated particles and the foamed particles are premixed and put into a single screw extruder. The screw speed is 6.6 rpm. The temperatures of each zone are: 85°C in zone 1, 101°C in zone 2, 100°C in zone 3, and 104°C in zone 4 to obtain a sheet, i.e., a pre-foamed body.
[0076] 5) The pre-foamed body is placed in a high-temperature foaming furnace at 260° C. for foaming to obtain a polyolefin foamed material.
[0077] Example 4 The components and mass fractions of the chemically cross-linked polyolefin foam material provided in this embodiment are as follows: 65 parts of polyolefin (low-density polyethylene, density 0.922 g / cm³, melt index 1.9 g / 10 min, purchased from Lanzhou Petrochemical 2426H), 15 parts of foaming agent (ADC foaming agent of Sopo Group, gas emission 215 mL / g), 0.5 parts of cross-linking agent (diisopropyl peroxide, 1 min decomposition half-life temperature 178 ℃, purchased from Hefei Anbang Chemical Co., Ltd.), 1 part of a cross-linking agent (trimethylolpropane trimethacrylate, with a specific gravity of 1.061g / cm³, purchased from Shanghai Dunmei New Materials), 0.5 parts of an antioxidant (antioxidant 1010), 11.25 parts of a brominated flame retardant (decabromodiphenylethane, with a particle size of 2μm and a mass percentage of bromine of 85%), and 3.75 parts of antimony trioxide / wollastonite composite powder (the mesh number of wollastonite is 300 mesh, the average particle size of nano antimony trioxide is 500nm, and the coverage rate of nano antimony trioxide on the surface of wollastonite is 75%). The preparation method of the above antimony trioxide / wollastonite composite powder is the same as that of Example 1, wherein the amount of 300 mesh needle-shaped wollastonite is 20g, the amount of antimony trichloride is 20g, the amount of surfactant PEG2000 is 0.2g, the reaction temperature is 50℃, and the reaction time is 0.5h.
[0078] The preparation method of the above chemically cross-linked polyolefin foam material is the same as that of Example 1.
[0079] Example 5 The components and mass fractions of the chemically cross-linked polyolefin foam material provided in this embodiment are as follows: 70 parts of polyolefin (polyolefin elastomer, density of 0.865g / cm³, melt index of 5g / 10min, purchased from ENGAGE 7447), 20 parts of foaming agent (ADC foaming agent of Sop Group, gas emission of 215mL / g), 1 part of cross-linking agent (dibenzoyl peroxide), 1.5 parts of auxiliary cross-linking agent (triallyl isocyanurate), 1 part of antioxidant (antioxidant CA), 11.25 parts of brominated flame retardant (decabromodiphenyl ether, particle size 2μm, mass percentage of bromine 83.3%), 3.75 parts of antimony trioxide / wollastonite composite powder (same as Example 4), 5 parts of (environmentally friendly flame retardant synergist FS-707R, purchased from Ruike New Materials). The preparation method of the antimony trioxide / wollastonite composite powder is the same as that in Example 1, wherein the amount of 500 mesh needle-shaped wollastonite is 20 g, the amount of antimony trichloride is 16 g, the amount of surfactant PEG2000 is 0.15 g, the reaction temperature is 48° C., and the reaction time is 1 h.
[0080] The preparation method of the above chemically cross-linked polyolefin foam material is the same as that of Example 1.
[0081] Example 6 The components and mass fractions of the chemically cross-linked polyolefin foam material provided in this embodiment are as follows: 60 parts of polyolefin (high-density polyethylene, density of 0.960g / cm³, melt index of 0.7g / 10min, purchased from Sinopec 5301B), 10 parts of foaming agent (azodicarbonamide, gas emission of 230mL / g), 0.2 parts of cross-linking agent (diacetyl peroxide), 0.5 parts of auxiliary cross-linking agent (trimethylolpropane triacrylate), 0.2 parts of antioxidant (antioxidant 330), 2.5 parts of brominated flame retardant (decabromodiphenylethane, particle size 2μm, mass percentage of bromine 85%), 2.5 parts of antimony trioxide / wollastonite composite powder (the mesh number of wollastonite is 500 mesh, the average particle size of nano antimony trioxide is 350nm, and the coverage rate of nano antimony trioxide on the surface of wollastonite is 67%).
[0082] The preparation method of the above chemically cross-linked polyolefin foam material is the same as that of Example 1.
[0083] Example 7 The components and mass fractions of the chemically cross-linked polyolefin foam material provided in this embodiment are as follows: 65 parts of polyolefin (polyolefin elastomer, density of 0.865g / cm³, melt index of 5g / 10min, purchased from ENGAGE 7447), 15 parts of foaming agent (azodicarbonamide, gas emission 230mL / g), 0.5 parts of cross-linking agent (di-tert-butyl peroxide diisopropylbenzene), 1 part of auxiliary cross-linking agent (trimethylolpropane trimethacrylate, specific gravity of 1.061g / cm³, purchased from Shanghai Dunmei New Materials), 0.5 parts of antioxidant (antioxidant 1010), 3.75 parts of brominated flame retardant (decabromodiphenyl ether, particle size 2μm, mass percentage of bromine 83.3%), 1.25 parts of antimony trioxide / wollastonite composite powder (same as Example 6).
[0084] The preparation method of the above chemically cross-linked polyolefin foam material is the same as that of Example 1.
[0085] Example 8 The components and mass fractions of the chemically cross-linked polyolefin foam material provided in this embodiment are as follows: 65 parts of polyolefin (polyolefin elastomer, density of 0.885g / cm³, melt index of 2g / 10min, purchased from Mitsui Chemicals A-1085S), 15 parts of foaming agent (ADC foaming agent of Sopo Group, gas emission of 215mL / g), 0.5 parts of cross-linking agent (tert-butyl peroxypivalate), 1 part of auxiliary cross-linking agent (trimethylolpropane triacrylate), 0.5 parts of antioxidant (antioxidant 1076), 3.75 parts of brominated flame retardant (decabromodiphenyl ether, particle size 2μm, mass percentage of bromine 83.3%), 1.25 parts of antimony trioxide / wollastonite composite powder (same as Example 6), 5 parts of (environmentally friendly flame retardant synergist FS-707R, purchased from Ruike New Materials).
[0086] The preparation method of the above chemically cross-linked polyolefin foam material is the same as that of Example 1.
[0087] Comparative Example 1 In the formula of the chemically cross-linked polyolefin foaming material provided in this comparative example, the antimony trioxide / wollastonite composite powder (the mesh number of the wollastonite is 500 mesh, the average particle size of the nano antimony trioxide is 80nm, and the coverage rate of the nano antimony trioxide on the surface of the wollastonite is 36%), and the rest is the same as in Example 1. The preparation method of the antimony trioxide / wollastonite composite powder is the same as in Example 1, wherein the amount of 500 mesh needle-shaped wollastonite is 20g, the amount of antimony trichloride is 9g, the amount of the surfactant PEG2000 is 0.05g, the reaction temperature is 40°C, and the reaction time is 1h.
[0088] The preparation method of the above chemically cross-linked polyolefin foam material is the same as that of Example 1.
[0089] Comparative Example 2 In the formula of the chemically cross-linked polyolefin foaming material provided in this comparative example, antimony trioxide / wollastonite composite powder (the mesh number of wollastonite is 500 mesh, the average particle size of nano antimony trioxide is 600nm, and the coverage rate of nano antimony trioxide on the surface of wollastonite is 80%), and the rest is the same as in Example 1. The preparation method of the antimony trioxide / wollastonite composite powder is the same as in Example 1, wherein the amount of 500 mesh needle-shaped wollastonite is 20g, the amount of antimony trichloride is 20g, the amount of surfactant PEG2000 is 0.3g, the reaction temperature is 50°C, and the reaction time is 1h.
[0090] The preparation method of the above chemically cross-linked polyolefin foam material is the same as that of Example 1.
[0091] Comparative Example 3 In the polyolefin foam material formula provided in this comparative example, the mass fraction of the brominated flame retardant is 9.5 parts, the mass fraction of the antimony trioxide / wollastonite composite powder is 2.5 parts, and the rest is the same as in Example 1.
[0092] The preparation method of the above chemically cross-linked polyolefin foam material is the same as that of Example 1.
[0093] Comparative Example 4 In the polyolefin foam material formula provided in this comparative example, the flame retardant is 12 parts of a brominated flame retardant, and the rest is the same as in Example 1.
[0094] The preparation method of the above chemically cross-linked polyolefin foam material is the same as that of Example 1.
[0095] Comparative Example 5 In the polyolefin foam material formula provided in this comparative example, the flame retardant is 12 parts of antimony trioxide / wollastonite composite powder, and the rest is the same as in Example 1.
[0096] The preparation method of the above chemically cross-linked polyolefin foam material is the same as that of Example 1.
[0097] Comparative Example 6 In the polyolefin foam material formula provided in this comparative example, 1.5 parts of antimony trioxide (average particle size of 230 nm) and 2.5 parts of 400-mesh wollastonite are used to replace 4 parts of antimony trioxide / wollastonite composite powder, and the rest is the same as in Example 1.
[0098] The preparation method of the above chemically cross-linked polyolefin foam material is the same as that of Example 1.
[0099] Comparative Example 7 In the polyolefin foam material formula provided in this comparative example, no co-crosslinking agent and antioxidant are added, and the rest is the same as in Example 1.
[0100] The preparation method of the above chemically cross-linked polyolefin foam material is the same as that of Example 1.
[0101] Comparative Example 8 The formula of the polyolefin foam material provided in this comparative example is the same as that of comparative example 7. Then, the chemically cross-linked polyolefin foam material is prepared according to the method provided in Example 1, wherein the foaming temperature in step (5) is 200°C.
[0102] The properties of the chemically cross-linked polyolefin foam materials prepared in Examples 1 to 8 and Comparative Examples 1 to 8 were tested, and the testing method was as follows: 1) Foaming ratio: Refer to ASTM3574-2017 Test A, use a balance and a thickness gauge to measure the density of polyolefin foam materials. The foaming ratio is the reciprocal of the density.
[0103] 2) Flame retardant grade: Cut the above polyolefin foam material into 10 150mm×50mm (length×width) flame retardant strips, and draw a mark line at 25mm, 60mm and 125mm from one end, then perform horizontal burning test on the flame retardant strips according to UL94 standard, and record the test results. The result judgment criteria are: ① If it goes out before the 125mm mark line or the burning speed is less than 40mm / min, it is judged as HBF grade; ② Among the five strips, at least four strips burn for no more than 2s, a single strip does not exceed 10s, and there are drops that ignite the cotton under the strips, it is judged as HF-2 grade; ③ Among the five strips, at least four strips burn for no more than 2s, a single strip does not exceed 10s, and there is no drop that ignites the cotton under the strips, it is judged as HF-1 grade.
[0104] 3) Afterflame time (T1) and afterglow time (T2): Refer to UL94 standard to test the afterflame time and afterglow time of a single polyolefin foam material sample.
[0105] 4) Residual amount of azodicarbonamide: Cut the above polyolefin foam material into pieces and place them in an extraction bottle. Use a mixed solvent of acetone and DMF (volume ratio of 1:1) as an extraction solvent to ultrasonically extract the azodicarbonamide in the sample, filter and collect the supernatant, and then use HPLC-DAD / MS to detect and analyze the supernatant. High performance liquid chromatography (HPLC) is used to separate the components of the supernatant, and then azodicarbonamide is qualitatively and quantitatively analyzed using a diode array detector (DAD) and mass spectrometry (MS) to calculate the residual amount of azodicarbonamide in the polyolefin foam material.
[0106] The test results are shown in Table 1.
[0107] Table 1 Properties of polyolefin foam materials prepared in Examples 1 to 8 and Comparative Examples 1 to 8
[0108] The experimental results show that by adding antimony trioxide / wollastonite composite powder as a flame retardant, and adjusting the average particle size of nano antimony trioxide in the antimony trioxide / wollastonite composite powder, the coverage of nano antimony trioxide on the surface of wollastonite, the mass ratio of bromine flame retardant and antimony trioxide / wollastonite composite powder, and other components such as co-crosslinking agent and antioxidant, the flame retardant polyolefin foam material can be improved while improving the foaming ratio, and a flame retardant polyolefin foam material with a high foaming ratio that meets the requirements can be prepared. In addition, the above-mentioned flame retardant can cooperate with other components such as co-crosslinking agent and antioxidant, so that the polyolefin material will not break when the sheet is foamed at high temperature, and the foaming agent is completely decomposed at high temperature, which can effectively solve the problem of excessive residual azodicarbonamide (content greater than 0.1%) of the foaming agent.
[0109] In Table 1, the flame retardant properties of the polyolefin foam materials prepared in Comparative Examples 1 and 2 are poor. The possible reason may be that in the antimony trioxide / wollastonite composite powder used in Comparative Example 1, the coverage rate of antimony trioxide on the surface of wollastonite is only 36%, and the synergistic flame retardant effect between the composite particles and the bromine-based flame retardant is weak, and the flame retardant properties of the polyolefin foam materials cannot be effectively improved; in the antimony trioxide / wollastonite composite powder used in Comparative Example 2, the coverage rate of antimony trioxide on the surface of wollastonite is 80%, and the particle size of antimony trioxide is too large, which makes the synergistic flame retardant effect of the composite particles and the bromine-based flame retardant worse.
[0110] Depend on Figure 2 It can be seen that the polyolefin foam material prepared in Comparative Example 6 has many bubbles on the surface and does not meet the requirement of surface smoothness. The reason for this may be that in Comparative Example 6, antimony trioxide is in direct contact with the foaming agent, causing the foaming agent to decompose in advance and generating more bubbles on the surface of the foaming material. In addition, the foaming ratio of Comparative Example 6 is significantly lower than that of Example 1. This may be because antimony trioxide reacts with the gas (such as ammonia) generated by the decomposition of the foaming agent, thereby reducing the overall gas emission, so that the overall foaming ratio of the polyolefin foam material is significantly reduced; while in the antimony trioxide / wollastonite composite powder used in Example 1, antimony trioxide is coated on the surface of wollastonite in a physical adsorption manner, and will not react with the gas (such as ammonia) generated by the decomposition of the foaming agent, thereby being able to prepare a polyolefin foam material with a high foaming ratio.
[0111] It will be easily understood by those skilled in the art that the above description is only a preferred embodiment of the present application and is not intended to limit the present application. Any modifications, equivalent substitutions and improvements made within the spirit and principles of the present application shall be included in the scope of protection of the present application.
Claims
1. A high foaming ratio and flame retardant chemically cross-linked polyolefin foam material, comprising a flame retardant, characterized in that: The flame retardant comprises a brominated flame retardant and antimony trioxide / wollastonite composite powder; In the antimony trioxide / wollastonite composite powder, nano antimony trioxide is attached to the surface of wollastonite in a physical adsorption manner, and the surface area covered by the nano antimony trioxide accounts for 40% or more of the total surface area of wollastonite.
2. The chemically cross-linked polyolefin foam material according to claim 1, characterized in that: The brominated flame retardant is selected from one or more of decabromodiphenyl ether, decabromodiphenyl ethane, tetrabromobisphenol A, hexabromocyclododecane, brominated epoxy resin and octabromoether; In the antimony trioxide / wollastonite composite powder, the surface area covered by nano antimony trioxide accounts for 40% to 75% of the total surface area of wollastonite; wherein the average particle size of the nano antimony trioxide is 100 to 500 nm, and the mesh size of the wollastonite is 300 to 600 meshes.
3. The chemically cross-linked polyolefin foam material according to claim 1 or 2, characterized in that: The mass ratio of the brominated flame retardant to the antimony trioxide / wollastonite composite powder is (1-3):
1.
4. The chemically cross-linked polyolefin foam material according to claim 1, characterized in that: The raw materials for preparing the chemically cross-linked polyolefin foaming material also include polyolefin, foaming agent, cross-linking agent, auxiliary cross-linking agent and antioxidant; Optionally, the mass ratio of the polyolefin, foaming agent, cross-linking agent, auxiliary cross-linking agent, antioxidant and flame retardant is (60~70):(10~20):(0.1~1):(0.5~1.5):(0.2~0.5):(5~15).
5. The chemically cross-linked polyolefin foam material according to claim 4, characterized in that: The polyolefin has a melt index of 0.5-5 g / 10 min and a density of 0.85-0.98 g / cm 3 and / or, The cross-linking agent is selected from one or more of dibenzoyl peroxide, diisopropyl di-tert-butyl peroxide, diisopropyl peroxide, diacetyl peroxide, tert-butyl peroxypivalate, and diphenyl peroxydicarbonate; and / or, The auxiliary cross-linking agent is selected from one or more of trimethylolpropane trimethacrylate, triallyl cyanurate, triallyl isocyanurate, and trimethylolpropane triacrylate; and / or, The antioxidant is selected from one or more of antioxidants CA, 330, 1010, and 1076.
6. The chemically cross-linked polyolefin foam material according to claim 1, characterized in that the raw materials for preparation further include a functional flame retardant; The functional flame retardant includes one or more of nano silicon dioxide, magnesium oxide, aluminum oxide, a silane coupling agent and pentaerythritol stearate.
7. The chemically cross-linked polyolefin foam material according to any one of claims 1 to 6, characterized in that: The foaming ratio of the chemically cross-linked polyolefin foam material is 25-45; The chemically cross-linked polyolefin foam material meets the UL94 horizontal combustion HF-1 grade, and the sum of the afterflame time and the afterglow time is ≤15s.
8. A method for preparing the chemically cross-linked polyolefin foam material according to any one of claims 4 to 7, characterized in that: The steps include: S1, mixing part of the polyolefin and the cross-linking agent, the auxiliary cross-linking agent, the antioxidant and the flame retardant, kneading the mixture and then extruding and granulating the mixture to obtain semi-formulated particles; S2, mixing and kneading the remaining polyolefin and the foaming agent, and then extruding and granulating them to obtain foamed particles; S3, extruding the semi-formulated particles and the expanded particles to obtain a sheet; S4, foaming the sheet to obtain a chemically cross-linked polyolefin foam material.
9. The preparation method according to claim 8, characterized in that: The temperature of the mixing and kneading in step S2 and the temperature of the extrusion molding in step S3 are both lower than the decomposition temperature of the foaming agent, and the temperature of the foaming in step S4 is higher than the decomposition temperature of the foaming agent.
10. The preparation method according to claim 9, characterized in that: The foaming temperature in step S4 is 240°C to 260°C.
Citation Information
Patent Citations
Application of flame-retardant anti-dripping agent taking natively wollastonite as resin composition and resin composition containing natively wollastonite
CN103772742A
Foamed polyolefin composition, polyolefin foamed material, preparation method thereof and product prepared from composition
CN104004259A
Flame-retarding polypropylene composition, preparation method, and application thereof
CN108102213A
Slightly foaming flame-retardant polyurethane material, and preparation method thereof
CN108341985A
Polyethylene material resistant to electron beam irradiation as well as preparation and application thereof
CN109306100A